Pengaruh Sosial Media Facebook Terhadap Bahasa Indonesia Siswa Kelas 7 Mts Islamiyah Sunggal - Edi Syahputra; Budiman Budiman; Akrizal Rifai (Universitas Dehasen Bengkulu, 2022)
The influence of Indonesian on Facebook social media has attracted attention to be studied, so this research aims to determine how much influence Facebook social media has on Indonesian from the use of standard and non-standard Indonesian and to find out how often 7th grade students of Mts Islamiyah Sunggal in using Indonesian in using social media Facebook. The sample in this study were 7th grade students of Mts Islamiyah Sunggal. This research method is a survey method by distributing questionnaires to students consisting of questions with answers. In the data analysis used is subjective by using google form. The results of this study indicate that many students are not affected by social media Facebook by using Indonesian which is not in accordance with the rules.